1986
DOI: 10.1093/clinchem/32.3.539
|View full text |Cite
|
Sign up to set email alerts
|

Dietary citric acid enhances absorption of aluminum in antacids.

Abstract: Ten healthy men ingested, twice daily between meals, during each of the seven-day experimental periods: (a) citric acid (as lemon juice), (b) Al(OH)3, or (c) Al(OH)3 + citric acid. Whole blood sampled after each dietary period was analyzed electrothermally after digestion with nitric acid. Moderate, but significant, increases in mean Al concentrations as compared with pretreatment values [5 (SD 3) micrograms of Al per liter] were seen after ingestion of either citric acid or Al(OH)3: 9 (SD 4) and 12 (SD 3) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2
2

Year Published

1990
1990
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(26 citation statements)
references
References 0 publications
0
22
2
2
Order By: Relevance
“…These may be due either to contamination, the source of which we were unable to determine, or more likely to high gastrointestinal absorption. Some predisposing factors for increased aluminium absorption, such as acidification or high citrate levels (Kirschbaum & Schoolwerth, 1989;Slanina et al, 1986) have been identified but we found no evidence of these in our subjects.…”
Section: Discussioncontrasting
confidence: 85%
“…These may be due either to contamination, the source of which we were unable to determine, or more likely to high gastrointestinal absorption. Some predisposing factors for increased aluminium absorption, such as acidification or high citrate levels (Kirschbaum & Schoolwerth, 1989;Slanina et al, 1986) have been identified but we found no evidence of these in our subjects.…”
Section: Discussioncontrasting
confidence: 85%
“…43 Th e citrate ligan d form s a series of stron g com plexes th at cross a broad pH spectru m an d th at com pete su ccessfu lly to bin d free Al (Figu re 6). 60 On e of th e Al-citrate com plexes presen t u n der acid con dition s is a n on polar m olecu le an d is presu m ed to be th e m ost readily tran sportable across th e in testin al m u cosa.…”
Section: Transformations In the Gutmentioning
confidence: 99%
“…Abnormal accumulation of aluminium has also been detected within the brain tissue of patients with Alzheimer's disease and the Parkinsonian dementia complex of Guam Perl et al, 1982;Candy et al, 1986). Aluminium salts also induce memory impairment in susceptible experimental animals, accompanied by the formation of neuronal cytoskeletal abnormalities (Klatzo et al, 1965; (2) The growing acidification of surface waters has led to augmented aluminium absorption (Cronan et al, 1986;Slanina et al, 1986). This has been linked to an increased incidence of Alzheimer's disease (Martyn et al, 1989).…”
Section: Introductionmentioning
confidence: 99%